2013
DOI: 10.1128/aem.00363-13
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Binding Module–Cyclodextrin Glycosyltransferase Fusion Enables Efficient Synthesis of 2- O - d -Glucopyranosyl- l -Ascorbic Acid with Soluble Starch as the Glycosyl Donor

Abstract: In this study, we achieved the efficient synthesis of 2-O-D-glucopyranosyl-L-ascorbic acid (AA-2G) from soluble starch by fusing a carbohydrate-binding module (CBM) from Alkalimonas amylolytica ␣-amylase (CBM Amy ) to cyclodextrin glycosyltransferase (CGTase) from Paenibacillus macerans. One fusion enzyme, CGT-CBM Amy , was constructed by fusing the CBM Amy to the C-terminal region of CGTase, and the other fusion enzyme, CGT⌬E-CBM Amy , was obtained by replacing the E domain of CGTase with CBM Amy . The two fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…The wild-type CGTase produced the highest AA-2G titer at 36°C, which was also reported in our previous work (9-11) and was similar to the optimal temperature for ␣-CGTase-catalyzed AA-2G synthesis with ␤-cyclodextrin as the glycosyl donor (7). However, for all mutant CGTases, the optimal temperature for AA-2G synthesis was 28°C, which was the same as that of the chimeric enzyme constructed by the fusion of CGTase to the carbohydrate-binding module (CBM) of A. amylolytica (CGT-CBM Amy ) and of the enzyme constructed by replacing the E domain of CGTase with that of CBM Amy (CGT⌬E-CBM Amy ) (11). Figure 3 shows the influence of pH on AA-2G synthesis by the wild-type and mutant CGTases.…”
Section: Construction Of Mutants By Ismmentioning
confidence: 99%
See 1 more Smart Citation
“…The wild-type CGTase produced the highest AA-2G titer at 36°C, which was also reported in our previous work (9-11) and was similar to the optimal temperature for ␣-CGTase-catalyzed AA-2G synthesis with ␤-cyclodextrin as the glycosyl donor (7). However, for all mutant CGTases, the optimal temperature for AA-2G synthesis was 28°C, which was the same as that of the chimeric enzyme constructed by the fusion of CGTase to the carbohydrate-binding module (CBM) of A. amylolytica (CGT-CBM Amy ) and of the enzyme constructed by replacing the E domain of CGTase with that of CBM Amy (CGT⌬E-CBM Amy ) (11). Figure 3 shows the influence of pH on AA-2G synthesis by the wild-type and mutant CGTases.…”
Section: Construction Of Mutants By Ismmentioning
confidence: 99%
“…This outcome suggested that mutagenesis was effective for improving the specificity of CGTase toward maltodextrin by affecting the hydrogen bond interactions between the enzymes and linear substrates. In addition, we enhanced the transformation efficiency of soluble starch to AA-2G by fusing a carbohydrate-binding module from Alkalimonas amylolytica ␣-amylase with CGTase from P. macerans (11).…”
mentioning
confidence: 99%
“…In summary, the enhanced soluble starch specificity for AA-2G synthesis was achieved via fusion of self-assembling amphipathic peptides to the N terminus of CGTase from P. macerans. Similarly, soluble starch substrate specificity was improved by fusing the carbohydrate-binding module of A. amylolytica ␣-amylase with CGTase from P. macerans in a previous study (11). These outcomes suggest that protein fusion technology is an effective approach to the modification of CGTase for AA-2G production.…”
Section: Methodsmentioning
confidence: 72%
“…2A, the optimal temperature for AA-2G production with the wild-type CGTase was 36°C, which was also reported in our previous studies (8)(9)(10) and is similar to the optimal temperature for ␣-CGTase-catalyzed AA-2G synthesis with ␤-cyclodextrin as the glycosyl donor (6). However, SAP5-CGTase and SAP6-CGTase produced the highest AA-2G titer at 28°C, and this optimal temperature is the same as that of production with the chimeric enzymes CGT-CBM Amy and CGT⌬E-CBM Amy (11). Figure 2B shows the influence of pH on AA-2G synthesis with the wild-type CGTase, SAP5-CGTase, and SAP6-CGTase with soluble starch as the glycosyl donor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation